On Characterizations of the Space of p-Semi-Integral Multilinear Mappings - Caliskan, Erhan (ARACNE EDITRICE, 2009)
In this paper we consider the ideal of p-semi-integral n-linear mappings, which is a natural multilinear extension of the ideal of p-summing linear operators. The space of p-semi-integral multilinear mappings is characterized by means of a suitable tensor norm up to an isometric isomorphism. In this connection we also consider tensor products of linear operators and multilinear mappings of finite type.
Keywords: p-semi integral multilinear mappings; tensor product of Banach spaces; Mathematics